Ora Viva, Ora Viva! Viva São Gonçalo Viva!: diferentes olhares e sentidos visuais - Rocha, Wádson Pereira (2020)
The permanence of collective memory regarding intangible heritage depends directly on human actions to identify, register, safeguard and perpetuate its content. The cultural manifestations that use the oral tradition and their narratives perish more easily when none of these actions are adopted, therefore, there must be a continuity of the transmission of these intangible goods among their people, taking measures that can guarantee and preserve them. It is imminent that a large part of the cultural baggage (the rules, customs, concepts and their peculiar facets) of São Gonçalo's dance is more present in practice than in formal teachings, so it is essential to search for looks and meanings visuals of this dance as a manifestation of culture part of a historically determined socio-cultural context; leaving aside the anachronistic thought that popular culture is a survivor of the past in the present. The Dance of São Gonçalo in Guaicuí, district of the municipality of Várzea da Palma-MG, walks in this work for the visualities about dance in the locality, its main peculiarities and characteristics of this doing. The failure to observe this type of context to deal with intangible heritage is what makes the discussions of this work relevant, in researching a cultural / traditional dance that is passed on from one generation to another. Therefore, the objective of this research is to understand and analyze the looks and visual meanings of the dance of São Gonçalo - for the langristas, the community, the students and this teacher / researcher - from Guaicuí. Therefore, the research arises from the observation of this professor to a promise paid to saint Gonçalo in the year 2017 and from the elaboration and writing of the annual lesson plan of art teaching for 2018, of the 1st year of high school, from the State School Guaicuí. The first conception started from the analysis of the effective participation of many students of this school organization in this cultural manifestation. The school is located in the center of the district, where this way of doing / dancing and sharing its values is remarkable, characteristics that are part of the everyday identity of those who make this dance a manifestation. The second conception was based on the federal legal principle of Law no. 11,645 / 2008, which obligatorily establishes, in art education, the study of indigenous and African history and culture, in elementary and high school. To this end, it was researched and observed that the Dance of São Gonçalo in this district carries with it identities of its Portuguese (Portuguese) origin, Amerindian and, mainly, African religious syncretism. In this sense, the research also seeks to understand the issues pertaining to belonging and identity to this culture. Given the contextualization that is access to technologies - the connected world - how does this dance, still, is a reference for the formative process and the construction of the cultural identity of these students? Thus, the research also aims to apprehend and abstract the social, cultural and aesthetic meaning of the different looks and meanings attributed to the Dance of São Gonçalo in Guaicuí. The students of this class will carry out fieldwork, raising them through orality and their narratives, trying to highlight the possible stories of families that have dance and / or the saint Gonçalo as their central axis. And, based on this data collection, the scope is to organize the oral and documentary data of this research to conceive a pedagogical proposal for a formative process in the construction of the cultural identity to be used by teachers and students of arts. It is necessary to expand the records based on oral tradition, corroborating the expansion of the repertoire of Portuguese-Brazilian dance. The surveys started in August 2018, with an expected end in August 2020. The survey has a qualitative approach and phenomenological method; the type of research is oral history and also narrative. It can be understood, hypothetically, that the results show that, although technological evolution has reached different places, including the town of Guaicuí, the São Gonçalo Dance is still a reference for the formation of identity, belonging and the formative path of students in that location.